Tracing the Rise of Galectin-3: A Global Bibliometric Insight Into Its Role in Heart Failure - Amjad Bani Hani; Alaa Tarazi; Lubna Alnatour; Ahmad Aburrub; Mohammad Hijah (International Journal of Vascular Medicine)
Conclusion: This is the first bibliometric analysis of publications on the association between galectin-3 and HF. This study provides researchers with valuable insights into the most influential articles on this biomarker and its role in HF. Key research areas focus on galectin-3 role in the diagnosis, pathology, and prognosis of various HF types, causes, and outcomes. Further research should explore how galectin-3 can facilitate earlier diagnosis of HF or fibrosis, with increased international collaboration among researchers.